Community and caregivers' perceptions of pneumonia and care‐seeking experiences in Nigeria: A qualitative study. Issue 1 (27th January 2020) - Bakare, Ayobami A.; Graham, Hamish; Agwai, Imaria C.; Shittu, Funmilayo; King, Carina; Colbourn, Tim; Iuliano, Agnese; Aranda, Zeus; McCollum, Eric D.; Isah, Adamu; Bahiru, Solomon; Valentine, Paula; et al.
Abstract: Background: Appropriate and timely care seeking can reduce pneumonia deaths, but are influenced by caregivers and community norms of health and illness. We explore caregiver and community perceptions, and care‐seeking experience, of childhood pneumonia, to understand contexts that drive pediatric service uptake in Nigeria. Methods: Community group discussions and qualitative interviews with caregivers in Lagos and Jigawa states were completed between 1 November 2018 and 31 May 2019. Participants were recruited from purposively sampled health facility catchment areas with assistance from facility staff. We used episodic interviews, asking caregivers (Jigawa = 20; Lagos = 15) to recount specific events linked to quests for therapy. Community group discussions (n = 3) used four vignettes from real pneumonia cases to frame a discussion around community priorities for healthcare and community‐led activities to improve child survival. Data were analyzed using the framework method. Results: We found poor knowledge of pneumonia‐specific symptoms and risk factors among caregivers and community members, with many attributing pneumonia to cold air exposure. Interviews highlighted that care‐seeking decision making involved both husbands and wives, but men often made final decisions. In Lagos, older female relatives also shaped quests for therapy. Cost was a major consideration. In both states, there were accounts of dissatisfaction with health workers' attitudes and a general acceptance of vaccination services. Conclusion: There is a need for community‐based approaches to improve caregiver knowledge and care seeking for under‐five children with pneumonia. Messaging should attend to knowledge of symptoms, risk factors, family dynamics, and community responsibilities in healthcare service delivery and utilization.